Proses Implementasi Kebijakan Pelembagaan Pengarusutamaan Gender (PUG) di Kota Padang - Arivo Adjivantara; Muhammad Ichsan Kabullah; Nila Wahyuni (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2026)
This article departs from the Padang city government’s failure to receive the Anugerah Parahita Ekapraya (APE) in 2023. This indicates ineffective implementation of gender mainstreaming (GM) policies in Padang City. The weakness of GM institutions in Padang City is one of the main aspects that makes the substance of PUG weak and less strategic. This is inseparable from the institutionalization process of GM as a mechanism for integrating a gender perspective throughout the policy, planning and budgeting cycles which is still being implemented in formal and technical orientations. The research approach used is qualitative case study, and data collection tehcniques using semi-structured interviews and library studies. From the findings obtained, it appears that institutionalization of GM proceeded partially with an orientation toward technical and administrative interactions. The GM institutionalization pro-cess emphasized formal compliance patterns without any substantive transformation. In terms of inputs, budgets and human resources were technically sufficient. However, due to weak political priorities and divisional capacity resulting from internal institutional fragmentation, resources could not be optimized. Consequently, the process side formed more ad-ministrative interactions with formal outputs and ultimately symbolic outcomes.